An Investigation Into the Price Increase Rapidly in Residential Property in the Johor Bahru - Ho, Nam Hon (2015)
In recently, it has been become harder to Malaysia citizen to own a home. In Johor Bahru, an average residential property prices in Johor rose 39.92 percent to RM275, 854 in 2013 from RM 197, 147 in 2012. There was an average home prices increase by about 7% from about RM457, 000 in 2012 to about RM489, 000. In the state of Selangor, mi average house prices increased by around 10% from RM307, 000 to RM339, 000. Housing price with 6% growth has exceeded expected household 4.7% income growth in the past decade. This scenario is shown that the properly price in Johor l3ahru is increasing rapidly. This research will focus on the factors of residential property prices increase rapidly in Johor E3ahru. The questionnaire have found that the majority of reason for owning a residential property was generally use for retirement planning, there were consistent with the highest ranking reason of long term capital gain. Besides, there were also found that the majority of respondents cited job opportunity was the main reason affecting residential property prices in the Johor Bahru. In terms of affordability to the housing prices, the research found that respondents generally felt that property prices were still neutral and the majority number of respondents from the survey (50%) felt that there was either strongly increase or excessive increase in residential property prices in the Johor Bahru from year 2009 to 2014, moreover the rate of residential property price increase was probably sustainable over the next few years.